The Determinant Factors of Auditor Switching - Dewi Indriasih (Monex: Journal of Accounting Research, 2022)
This study is aimed at analizing the effect of management change, financial distress, going concern audit opinion, company size, and the size of public accounting firms on auditor switching. Changes in auditors are carried out so that the independence of the KAP can be increased so that there is no dependence between them and to produce an objective audit opinion. The population in this study were 86 non-cyclical primary consumer goods companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique is the purposive sampling method which produces a sample of 22 companies which are included in the group of manufacturing companies in the food and beverage sub-sector. This type of research is descriptive quantitative. The data analysis method used descriptive statistical analysis and logistic regression analysis. The results of this study indicate that only the change in management variable has an effect on auditor turnover. Meanwhile, other variables in the study, such as financial distress, going concern audit opinion, company size, and the size of the public accounting firm, have no effect on auditor switching. The results of the research can contribute to economic and information material for the public accounting profession regarding the practice of changing auditors, as well as providing knowledge and insight on auditing development, especially regarding auditor turnover.